Guest

if m,n be the roots of equation (x-a)(x-b)+c=0(c not =0).then the roots of equation (x-c-m)(x-c-n)=c 1)a,b+c 2)a+c,b 3)a+c,b+c 4)a-c,b-c

if m,n be the roots of equation (x-a)(x-b)+c=0(c not =0).then the roots of equation (x-c-m)(x-c-n)=c
1)a,b+c 2)a+c,b 3)a+c,b+c 4)a-c,b-c

Grade:Upto college level

1 Answers

sanatan sharma
26 Points
10 years ago

the answer is third i.e. a+c , b+c .


Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free